Pemberdayaan Pemuda Karang Taruna di Kelurahan Cipedak Jagakarsa Melalui Pelatihan Instalasi Listrik Rumah Sederhana - Irmayani Irmayani; Djoko Priambodo; Achmad Muhyidin Arifai; Muhamad Alvin Aufar; M. Fahmi Arsyad; Heriyanto Wibowo; Agus Nugroho; Gendoet Indarto Wibisono; Haniva Mulyani (ASPIRASI : Publikasi Hasil Pengabdian dan Kegiatan Masyarakat, 2023)
This community service activity aims to empower the youth of Karang Taruna in Rukun Warga 06, Cipedak area, Jagakarsa, South Jakarta, through training in basic home electrical installation. The empowerment initiative is expected to enhance the participants’ technical skills and economic independence in facing the challenges of the job market, particularly in the electrical sector, which offers broad prospects. The implementation methods include material delivery/counseling sessions, hands-on practical training, and participant skill evaluation. The results of the activity show an increase in participants' understanding of basic electrical installation and adequate practical skills applicable at the household level. Participant success was assessed based on their ability to assemble electrical circuits and conduct electricity through prepared media, as indicated by the illumination of light bulbs in each installed circuit. This activity has had a positive impact in shaping more productive youth who are ready to compete in the workforce, while also contributing to community-based local development. The results of the counseling and training on electrical installation for simple houses showed that 80% of the participants were able to carry out residential electrical installations properly and in accordance with the PUIL 2000 standards.